Water Fertility Based on Chlorophyll a in Aqua-MODIS Satellite Imagery in the Waters of Belitung Island - Valentin Vina Ratnapuri; Monischa Br Sebayang; Misri Yandi; Ali Rizki Maulana; Ni Luh Eta Yuspita (International Journal of Science and Environment (IJSE), 2026)
The waters of Belitung Island are tropical waters that play a crucial role in supporting the global ecosystem balance through primary productivity, which can be measured using chlorophyll a concentration as an indicator of water fertility. The strategic geographical location of Belitung Island, situated on the border of the Karimata Strait, the Java Sea, and the South China Sea, makes it vulnerable to the constantly changing oceanographic dynamics. This study aims to analyze the spatial-temporal distribution and fluctuations of chlorophyll a in the waters of Belitung Island based on Aqua-MODIS satellite imagery from January to December 2024. Chlorophyll-a data were extracted from Aqua-MODIS satellite imagery using the OCx and CI algorithms, then analyzed using the Inverse Distance Weighting (IDW) interpolation method through ArcGIS and SeaDAS software. The research results show that the waters of Belitung Island are generally classified as oligotrophic, with an average chlorophyll a concentration ranging from 0.39 to 0.81 mg/m³. The lowest concentration at the April location point was 0.08 mg/m³, and the lowest average was in May (0.39 mg/m³), coinciding with the first transition season due to reduced upwelling and water stratification. Conversely, the highest concentration was detected at the May location point (5.14 mg/m³), and the highest average was observed in June (0.81 mg/m³), when the southeast monsoon triggered increased winds and upwelling, bringing nutrients from the lower layers to the surface. This research demonstrates that monsoon variability and local oceanographic processes have a significant influence on water fertility in Belitung Island and can be utilized in predicting potential fishing areas.